Chimeric antigen receptor (CAR) -T cell therapy treatment Richter's transformation - Feng, Shaomei; Zheng, Peihao; Liu, Haidi; Sun, Meiling; Guo, Yuelu; Ma, Lixia; Liu, Rui; Fu, Zhonghua; Yang, Fan; Ke, Xiaoyan; Hu, Kai (Frontiers in Oncology, 2025)
Background/purposeDespite advances in chronic lymphocytic leukemia treatment, effective therapies for cases with Richter’s transformation (RT) are urgently needed. This study aimed to investigate the use of chimeric antigen receptor (CAR)-T cell infusion for RT.MethodsThis study included RT patients at Beijing Boren Hospital between February 2020 and February 2023. Complete response (CR), partial response (PR), overall response rate (ORR), overall survival (OS), progression free survival (PFS), and adverse events were analyzed.ResultsData from 16 patients with RT who underwent CAR-T cell therapy [62.5% (10/16) males and a median age of 59 years (range: 42–69 years)] were collected. The 3-month CR rate was 56.3% (9/16), with an ORR of 68.8% (11/16). Median follow-up was 19.1 months (4.37-42.48m), the 1-year OS/PFS were 75.0%/68.8%, and the 2-year OS/PFS were 67.5%/61.1%. Among 11 patients with CR (n=9) and PR (n=2), 1 CR case died of an acute coronary event, 10 patients had no recurrence or progression at a median follow-up of 24.6 months. Five patients who did not respond to CAR-T cell therapy had a median OS of only 6.44 months. Univariate logistic regression analysis showed ECOG score [odds ratio (OR)=0.025, P=0.016] were independently associated with ORR. ECOG (OR=40, P=0.016) were independently associated with OS. The presence of an extramedullary mass larger than 5cm did not show statistical significance for overall survival (OS), although the P value was close to 0.05 (OR=15, P=0.051).ConclusionsCAR-T cell therapy showed potential as a treatment for RT. ECOG score may be independently associated with ORR and OS. RT patients may experience prolonged remission and achieve long-term disease control if they attain remission through chimeric antigen receptor T-cell therapy.